Pandangan Islam terhadap Pemakaian Kemenyan pada Masyarakat Suku Jawa Studi Kasus Desa Laugambir Kecamatan STM Hilir Kabupaten Deli Serdang - Febriyanti, Wulan (ANWARUL, 2023)
This research is entitled about the Islamic view of the use of incense in the Javanese community. This research is a qualitative research oriented to field research (Library Research) using an Anthropological approach, and the theory is Ethnicity. Sources of data generated from the results of interviews, observations, and documentation. The results of this study indicate that in Laugambir Village, burning incense is a ritual that has been going on for a long time and is part of everyday life. However, local residents are not even sure of the origin of this custom of burning incense. This practice of burning incense is carried out many times at various events, such as grave pilgrimages, celebrations of the Prophet's birthday, peusijuk assemblies, votive contests, and so on. No special equipment is required for the incense burning procession itself, and no special individual or individuals are required to burn the incense. However, locals usually delegate it to their elders or those who are familiar with the prayers involved in the incense burning ritual. There are some people who do not want to take part in this procession for fear that they will deviate from asking for the incense smoke. In this tradition, basically there are many pros and cons both in terms of opinion and the implementation of the incense burning procession in people's lives. However, the literal meaning is to invoke and pray to God through the use of incense.